2015
DOI: 10.1111/wbm.12084
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of the weed species,Stellera chamaejasme, inChina inferred from amplified fragment length polymorphism analysis

Abstract: Stellera chamaejasme is a perennial weed with a wide geographic range that is found from the Altai of eastern Russia, northern China and Mongolia southwards as far as the western Himalayas of the Qinghai-Tibet and Yungui Plateaus. The genetic diversity and population structure of 17 populations of S. chamaejasme, represented by 349 individuals, were assessed by using amplified fragment length polymorphism markers. The results showed a relatively high level of genetic variation at the species level. The proport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 42 publications
3
5
0
Order By: Relevance
“…The relatively low predictive power of the model of QT suggested that most variation remained unexplained. We found that S. chamaejasme could survive in a soil environment with considerable variation, which is consistent with the fact that S. chamaejasme is wide-ranging species with a wide geographic range in China grassland (Zhang et al 2015). The soil condition for S. chamaejasme growth varies considerably from site to site.…”
Section: Relative Roles Of Soil and Climatic Factorssupporting
confidence: 82%
“…The relatively low predictive power of the model of QT suggested that most variation remained unexplained. We found that S. chamaejasme could survive in a soil environment with considerable variation, which is consistent with the fact that S. chamaejasme is wide-ranging species with a wide geographic range in China grassland (Zhang et al 2015). The soil condition for S. chamaejasme growth varies considerably from site to site.…”
Section: Relative Roles Of Soil and Climatic Factorssupporting
confidence: 82%
“…We found that S. chamaejasme could survive in a soil environment with considerable variation, which is consistent with the fact that S. chamaejasme is wide-ranging species with a wide geographic range in China grassland [43]. The soil condition for S. chamaejasme growth varies considerably from site to site.…”
Section: Overall Patterns Of Leaf Ecological Stoichiometry and Soil Physicochemical Properties Of S Chamaejasme Across Northern Chinasupporting
confidence: 82%
“…In turn, investigations using microsatellite markers showed that H e ranged from 0.36 to 0.82, while the polymorphism information content (PIC) ranged from 0.33 to 0.80 (Lema-SuĂĄrez et al 2016). Significant differences in genetic variability among populations located in the centre and at the species natural range limit have already been repeatedly demonstrated (e.g., Eckert et al 2008;Zhang et al 2015).…”
Section: Discussionmentioning
confidence: 84%